Patrolling Mechanics of Non-Classical Monocytes in Vascular Inflammation - Buscher, Konrad; Marcovecchio, Paola; Hedrick, Catherine C.; Ley, Klaus (Frontiers in Cardiovascular Medicine, 2017)
Nonclassical monocytes have emerged as the pre-eminent vascular housekeepers. Continuous intravascular screening is enabled by slow patrolling on the endothelium and allows a rapid response to local perturbations. Intravital imaging has been crucial to elucidate the molecular mechanisms and migratory patterns of patrolling. In this review we discuss technical requirements of intravital microscopy such as imaging modalities, labeling strategies and data analysis. We further focus on patrolling kinetics and adhesion receptors in different organs and vascular beds including arteries during homeostasis and vascular inflammation, and define pertinent questions in the field.